The effectiveness of Participatory Drugstore Network on Standard Improvement of Drugstores in Chon Buri - Prasertthaicharoen, Ratikorn (Journal of Health Science of Thailand, 2018)
Even the Pharmacy Council and Food and Drug Board had collectively developed standard criteria as a tool for a project on development and accreditation of pharmacy since 2003 not one single establishment in Chon Buri was qualified. Most were non-advocates. This survey of all 385 drugstores was to evaluate the effectiveness of participatory drugstore network in the accreditation process in Chon Buri based on a set of evaluation from collectively developed during January 2006-December 2007. In data analysis, descriptive statistics were employed, Participation of the drugstore network, and a pharmacist club was essential through the accreditation process not only on defining the standard criteria but also the consultative meetings, actual assessment and a series of improvement. Impressive advocacy could be observed as a number of pharmacies classified as excellent (scoring over 80%) increased from 57.2 percent at the beginning to 8.31 in the end Presently 7 pharmacies in that category were accredited by the Pharmacy Council with strong incentive from the network The participatory process is highly recommended in accreditation of other types of establishments.